Dadih Susu Sapi Hasil Fermentasi Berbagai Starter Bakteri Probiotik yang Disimpan pada Suhu Rendah: II. Karakteristik Fisik, Organoleptik dan Mikrobiologi - E Taufik (Faculty of Animal Science, Bogor Agricultural University, 2005)
This research was conducted to investigate physical, organoleptical and microbiological characteristics of dadih from cow milk fermented with different combinations of probiotic starter bacteria and stored at low temperature. The concentration of starter used to make dadih was 3% with equal comparison between starters. The combinations of probiotic starter bacteria were (L. plantarum (A1), L. plantarum + L. acidophilus (A2), L. plantarum + B. bifidum (A3) and L. plantarum + L. acidophilus + B. bifidum (A4)) and stored at low temperatures (refrigerator) for 0, 7 and 14 days. The observed variables were viscosity, total lactic acid bacteria, total Bifidobacterium bifidum and organoleptic properties (color, aroma, taste and firmness). The result showed that combinations of probiotic starter bacteria did not affect significantly (P > 0.05) viscosity and total Bificobacterium bifidum of dadih at H-0 (before storage), but affect significantly (P < 0.05) total lactic acid bacteria. The characteristics of dadih during 14 days of storage in low temperature showed that combinations of starter did not significantly affect viscosity but storage time affect significantly (P < 0.05). Total Bificobacterium bifidum was not affected significantly by either starter combination or storage time.Total lactic acid bacteria was significantly affected (P < 0.05) by storage time and very significantly affected (P < 0.01) by starter combinations. A4 starter combination (L. plantarum + L. acidophilus + B. bifidum) has the most preference modus value for firmness, color, flavor and aroma according to panelist test result. Among those four organoleptic parameters, only aroma was affected significantly by starter combination. Key words: dadih, cow milk, probiotic, lactic acid bacteria, characteristic